Pengaruh Sales Promotion dan Price Discount terhadap Impulsive Buying pada Toko Fillyshop Tanah Grogot Kabupaten Paser - Indri Farradina; Ibnu khayath Farisanu; Bethania Angelica Khetreen (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyze the effect of Sales Promotion and Price Discount on Impulsive Buying at Fillyshop in Tanah Grogot, Paser Regency. The phenomenon of impulse buying, which has become increasingly common in the fast fashion era, is the focus of this research, considering that aggressive promotional strategies and price discounts are frequently used to attract consumer attention. The population in this study includes all consumers who made purchases at Fillyshop during December 2024. The sampling technique used was incidental sampling, with a total of 30 respondents. This research adopts a quantitative approach using a survey method through questionnaires. The data were analyzed using multiple linear regression, multiple correlation analysis (R), coefficient of determination (R²), and t-test and F-test, processed using SPSS software. The regression analysis results indicate that both Sales Promotion and Price Discount have a significant effect on Impulsive Buying, with Price Discount being the dominant variable. The Adjusted R Square value of 0.887 indicates that 88.7% of the variance in impulsive buying can be explained by the variables studied. The implications of this study emphasize the importance of pricing promotion strategies in driving consumers’ spontaneous purchase decisions and the need to enhance creativity in sales promotions to support the growth of the fashion retail business.